The comparison of working culture at local and foreign company in Malaysia / Shahrizan Sulaiman - Sulaiman, Shahrizan (2011)
The study was conducted at Amanah Saham Nasional Berhad (ASNB) located at Jalan Tun Razak, Kuala Lumpur and Standard Chartered Bank Malaysia Berhad located at Jalan Sultan Ismail. The study conducted focusing on “The Comparison of Working Culture at Local and Foreign Company.” Researcher had distributed the questionnaires to the workers in Unit Trust Department at both companies, ASNB and Standard Chartered Bank Malaysia Berhad. There are 30 respondents for each company in order to obtain the findings regarding the topic. The objective of this study is to investigate the relationship between the individualism, masculinity, uncertainty avoidance and power distance with working culture. Besides that, researcher want to identify the most influenced independent variables in working culture and to identify gap between foreign and local company in working culture.